Risk of all-cause mortality associated with chronic obstructive pulmonary disease and the role of healthy ageing trajectories: a population-based study of middle-aged and older adults - Josep Maria Haro; Daniel Fernandez; Ivet Bayes-Marin; Albert Sanchez-Niubo; Beatriz Olaya (BMJ Open)
Objectives The aims were to study the risk of all-cause mortality associated with chronic obstructive pulmonary disease (COPD) and healthy ageing trajectories (HAT) in three birth cohorts and to determine the moderating role of HAT in the association between COPD and all-cause mortality.Design Prospective cohort study.Setting Data from waves 1 to 5 of The Survey of Health, Ageing and Retirement in Europe.Participants The total sample was 28 857 community-dwelling individuals aged 50+ years.Main outcome All-cause mortality associated with COPD and HAT adjusting for covariates. We performed Aalen additive hazards models to explore these associations. Interactions between COPD and HAT were also explored. Analyses were conducted separately in three birth cohorts (>1945, 1936–1945 and ≤1935). Latent class growth analysis was used to classify participants into HAT.Results Three parallel HAT were found in the three birth cohorts (‘low’, ‘medium’ and ‘high’ healthy ageing). Participants with COPD had an increased mortality risk, but this effect was no longer significant after adjusting for covariates. The ‘low’ HAT was associated with increased mortality risk in the three subsamples, although this effect was lower after adjustment. The interaction between COPD and HAT was significant only in the ≤1935 birth cohort, indicating that those with COPD and a ‘low’ trajectory had a greater risk of mortality.Conclusions The healthy ageing scale may be a suitable tool to identify patients at higher risk to mitigate disease burden and improve patients’ quality of life.